Profitabilitas PT BCA Syariah : Analisis Determinan Dana Pihak Ketiga, Modal Dan Financing To Deposit Rasio - Husni Shabri; Anggia Nofasari (Al-bank: Journal of Islamic Banking and Finance, 2022)
This study aims to analyze the effect of Third Party Funds and Capital on the Net Profit of PT BCA Syariah for the period 2011-2020 with the Financing to Deposit Ratio as the Intervening variable. This type of research is quantitative research with quantitative descriptive methods. Data collection techniques using documentation with secondary data sources in the form of quarterly financial statements of PT BCA Syariah. The data analysis technique used path analysis which was processed with SPSS 26 software. The results showed that Third Party Funds directly had a significant influence on the Net Profit of PT BCA Syariah. Likewise, capital directly has a significant effect on Net Profit. Third Party Funds and Capital indirectly through the Financing to Deposit Ratio have no effect on the Net Profit of PT BCA Syariah for the 2011-2020 period. This research can be an input for PT BCA Syariah in making policies related to increasing company profitability